Pandemics and Traditional Plant-Based Remedies. A Historical-Botanical Review in the Era of COVID19 - Garcia, Sònia (Frontiers in Plant Science, 2020)
Pandemics are as old as humanity and since ancient times we have turned to plants to find solutions to health-related problems. Traditional medicines based mostly on plants are still the only therapeutic possibility in many developing countries, but even in the richest ones, herbal formulation currently receives increased attention. Plants are natural laboratories whose complex secondary metabolism produces a wealth of chemical compounds, leading to drug discovery – 25% of widespread use drugs are indeed of plant origin. Their therapeutic potential is even bigger: although many plant-based compounds show inhibitory effects against a myriad of pathogens, few reach the stage of clinical trials. Their mechanism of action is often unknown, yet traditional plant-based remedies have the advantage of a long-term experience in their use, usually of hundreds to thousands of years, and thus a precious experience on their safety and effects. Here I am providing a non-systematic historical-botanical review of some of the most devastating pandemics that humanity has faced, with a focus on plant therapeutic uses. I will revisit the Middle Ages black death, in which a plant-based lotion (the four thieves vinegar) showed some effectiveness; the smallpox, a viral disease that lead to the discovery of vaccination but for which the native Americans had a plant ally, an interesting carnivorous plant species; tuberculosis and the use of garlic; the Spanish flu and the widespread recommendation of eating onions, among other plant-based treatments; and malaria, whose first effective treatment, quinine, came from the bark of a Peruvian tree, properties already known by the Quechua people. Synthetic analogues of quinine such as chloroquine or hydroxychloroquine are now being revisited for the treatment of COVID19 symptoms, as they are artemisinin and derivatives, other plant-based compounds effective against malaria. Finally, I will give some hints on another facet of plants to aid us in the prevention of infectious diseases: the production of biotechnological plant-based vaccines. Altogether, my aim is to stress the significant role of plants in global health (past, present and future) and the need of enhancing and protecting the botanical knowledge, from systematics to conservation, from ecology to ethnobotany.